Strategi Kepala Sekolah dalam Mengembangkan Sarana Pendidikan di MTSN 2 Cirebon - Nur Alifah, Nur Alifah - (IAIN Syekh Nurjati Cirebon, 2021)
ABSTRACTThe problem of educational facilities is basically complex. Schools are required to have independence to regulate and manage the interest of the school. According to their own needs and abilities and based on quality, aspirations and participation of school resident continue to refer to applicable national education laws and regulations. The principal as a leader plays an important role in managing the facilities at the school in order to support his learning activitie s at school. For this reason this research was conducted, explaining the importance of the participal’s role and the principal’s strategy in developing educational facilities. This research in based on the SISDIKNAS law and corcerned theory. Research approach using qualitative research. Data collection techniques though participant observation, in-depth interviews and documentations. Technical analysis of qualitative data through data reduction, data presentation and conclusion drawing. Based on the results of the research that : 1) The principal has done his part in developing education facilities in MTs Negeri 2 Cirebon City.2) The strategy under taken by school principals in developing educational facilities is by forming special taems, collaborations with other institutions or againcies. 3) The inhibiting factor for school principals in developing educational facilities is the length of disbursement of funds from the goverment, while supporting factors for school principals in developing educational facilities is the incomplete facilities available in schools to support learning activities.Keywords: Strategy, Principal, Education facilities. ABSTRAKMasalah sarana pendidikan pada dasarnya cukup kompleks. Sekolah dituntut memiliki kemandirian untuk mengatur dan mengurus kepentingan sekolah menurut kebutuhan dan kemampuan sendiri serta berdasarkan mutu, aspirasi dan partisipasi warga sekolah tetap mengacu pada peraturan dan perundang-undangan pendidikan nasional yang berlaku. Kepala sekolah sebagai pemimpin, berperan penting dalam mengelola sarana yang terdapat disekolah demi menunjangnya kegiatan pembelajaran disekolah.Untuk itulah penelitian ini dilakukan, memaparkan pentingnya peran kepala sekolah dan strategi kepala sekolah dalam mengembangkan sarana pendidikan. Penelitian ini didasarkan pada undang-undang sisdiknas dan teori prihatin. Pendekatan penelitian menggunakan penelitian kualitatif. Teknik pengumpulan data melalui obserfasi partisipan, wawancara mendalam dan dokumentasi. Teknis analisi data kualitatif melalui reduksi data, penyajian data dan penarikan kesimpulan. Berdasarkan hasil penelitian bahwa: 1) kepala sekolah sudah melakukan peranannya dalam mengembangkan sarana pendidikan di MTs Negeri 2 Kota Cirebon. 2) Strategi yang dilakukan kepala sekolah dalam mengembangkan sarana pendidikan yaitu dengan cara membentuk tim khusus, kerjasama dengan komite sekolah, dan kerjasama dengan lembaga atau instansi lain. 3) Faktor penghambat kepala sekolah dalam mengembangkan sarana pendidikan yaitu lamanya pencairan dana dari pemerintah, sedangkan faktor pendukung kepala sekolah dalam mengembangkan sarana pendidikan yaitu belum lengkapnya fasilitas yang terdapat disekolah untuk menunjang kegiatan pembelajaran.Kata Kunci: Strategi, Kepala Sekolah, Sarana Pendidikan.